Current Works - Bernal Arango, Alejandro (2019)
This research work explores the relationship of Art and Science from the concept of Uncertainty. Uncertainty is the source of inspiration that drove the author to embark on a journey of discovery within two rather unknown fields to him, Glass and Electricity. The analogy made in this thesis between Glass and Electricity and Art and Science is a personal search for understanding the nature of the world, a dive into both the certainty of rational experimentation in the Scientific method, and the innate uncertain nature of experimentation in Art-making. This work is in essence a mirror that reflects the nature of the author’s mind, making visible some interesting ideas, impossible dreams, failed attempts and small discoveries. But above all, it’s a story of personal resilience, the search for a meaningful ‘ground’ and the ‘connection’ between Art and Science. In terms of practical goal, this study begins with fundamental considerations about how to achieve a new working method for Glass Printing formed from raw materials using controlled electric discharges.